Кристаллическая структура диборида алюмини в композитах КНБ, полученных реакционным спеканием при высоких давлениях - Беженар, Н.П.; Божко, С.А.; Белявина, Н.Н.; Маркив, В.Я.; Шульженко, А.А. (Видавничий дім "Академперіодика" НАН України, 2007)
The crystal structure of aluminum diboride obtained (at high pressures and high temperatures) by the sintering of initial aluminum and boron powders, as well as of aluminum and boron nitride powders, is reﬁned by using X-ray diﬀraction method. It is shown that the reactive interaction leads to the formation of solid solutions of light components (N, O, C) on the base of the nonstoichiometric compound ≈ Al0.9B2.